Die Weimarer Republik : Deutschlands erste Demokratie - Klußmann, Uwe 1961- Herausgeber; Berg, Stefan 1964- Mitwirkender; Mohr, Joachim 1962- Herausgeber; Deutsche Verlags-Anstalt (Dt. Verl.-Anst, 2015)
Mit Personenregister